Science Education: A Vital Tool for Promoting National Security for Sustainable Development - Usman Rufai Fakai; Ibrahim Musa Namagare; Zeenat Abdullahi; Nuhu Umar Dabai (International Journal of Integrative Research, 2023)
Science education enables learner to acquire certain skills and own the proper kind of values and attitudes vital for nonviolent coexistence and resolution of some security problems in the society. This paper discuss how science education can serve as a tool for promoting National security, it also highlight some of the factors that causes insecurity and how science education can help resolve some of the challenges of national security in Nigeria. The paper concludes that for sustainable and long lasting security, it is imperative to employ scientific approach such as developing new security paradigm and protocols in fighting violent conflicts and tackle insecurity in the country. The paper also point out the need to provide moral leadership that shun evil, corruption, vices, inequity, injustice and wickedness as this will compel the people to model the character of their leaders and vice versa. Democratic system in place must also begin to deliver the needed social goods so as to improve the standard of living of Nigerians and deliver many citizens from the state of abject poverty to which they have been subjected for a long while